On Keats's Practice and Poetics of Responsibility Beauty and Truth in the Major Poems - Atkins, G. Douglas; SpringerLink (Online service) (Cham : Springer International Publishing(Imprint), 2016)
This accessible, informed, and engaging book offers fresh, new avenues into Keats's poems and letters, including a valuable introduction to "the responsible poet." Focusing on Keats's sense of responsibility to truth, poetry, and the reader, G. Douglas Atkins, a noted T.S. Eliot critic, writes as an ama-teur. He reads the letters as literary texts, essayistic and dramatic; the Odes in comparison with Eliot's treatment of similar subjects; "The Eve of St. Agnes" by adding to his respected earlier article on the poem an addendum outlining a bold new reading; "Lamia" by focusing on its complex and perplexing treatment of philosophy and imagination and revealing how Keats literally represents philosophy as functioning within poetry. Comparing Keats with Eliot, poet-philosopher, this book generates valuable insight into Keats's successful and often sophisticated poetic treatment of ideas, accentuating the image of him as "the responsible poet.".
Preface -- One: On Putting Keats in Other Words: Essaying toward Reader-Responsibility -- Two: Reading the Letters: "The Vale of Soul-Making" -- Three: Some of the Dangers in "Unperplex[ing] bliss from its neighbour pain": Reading the Odes Intra- and Inter-textually -- Four: Fleeing into the Storm: Beauty and Truth in "The Eve of St. Agnes" -- Five: "For Truth's Sake": "Lamia" and the Reweaving of the Rainbow -- Bibliography -- Index. .
Keywords: POETRY; Literature, Modern-19th century; Literature-History and criticism